Comparison of consonant clusters and diphthongs in the language Betawi and Indonesian - Ila Nafilah; Yulia Agustin; Sulis Setiawati (Universitas Indraprasta PGRI, 2017)
Language is an interaction tool used by humans to be able to interact with each other. Without language, communication can not take place as it should. Misconceptions among members of a particular group of people are caused by the inability to interpret the speaker's intent and purpose in discussing a topic of conversation. The language is unique, meaning that each language develops its own rules that ultimately distinguish one language from another, as well as Betawi and Indonesian. This study aims to find out the comparison of consonant and diphthong groups in Betawi and Indonesian. This research was conducted in Jakarta and the research time started from September to December 2016. The focus of this research is on comparison of consonant and diphthong groups in Betawi and Indonesian. The object of this research is Betawi language vocabulary and Indonesian language. Research with this qualitative approach using content analysis method (content analysis). In this study, which will be the subject of research is Betawi language vocabulary derived from three sources, namely Betawi Glossary book written by Ridwan Saidi published by Betawi Ngeriung in Jakarta in 2007, book of Daily Dictionary of Betawi Language written by Sukanta published by Grasindo in Jakarta In 2010 and the Indonesian language vocabulary sourced from KBBI.